Schaum's outline of theory and problems of advanced calculus - Robert C. Wrede (Schaum's outline series., 2005)
This best-selling guide--which has sold more than 340,000 copies since its first publication--has been thoroughly updated throughout to correspons to current advanced calculus courses. A complete and comprehensive review of the subject, this updated edition features important new chapters on topology and Laplace transforms and essential new theorems, with explanatory proofs.